Qualidade de vida, do sono e percepção subjetiva da dor e incapacidade funcional em praticantes de taekwondo com e sem lesões musculoesqueléticas - SOARES, Itânio da Silva (2025)
Introduction: Taekwondo is a fighting, martial art, and combat sport whose practice involves a risk of musculoskeletal injuries and pain that may influence practitioners' perception of quality of life. Objective: To analyze the association between quality of life, sleep and subjective perception of pain in Taekwondo practitioners with and without musculoskeletal injuries. Materials and methods: The following instruments were used for data collection Questionnaire on Injuries in the Practice of Fighting, Martial Arts and Combat Sports (QLGS1), with sociodemographic and anthropometric information, about the modality and about injuries; the Medical Outcomes Study, Short Form-36 (SF-36) quality of life questionnaire; and the sleep quality questionnaire, Pittsburgh Sleep Quality Index (PSQI); and the Self-Estimated Functional Inability because of Pain (SEFIP-sport). Results: There was a predominance of young people (24.0±9.7 years of age), men (68.1%), residents of São Luís (89.9%), with complete high school (39.1%) and monthly family income of up to one minimum wage (30.4%) and eutrophic body mass index (23.6±5.6 kg/m2). Among the occurrence of injuries (59.4%), knee injuries were the most reported (27.5%), with dislocations (31.7%) and contusions (31.7%) most frequent, occurring in competitions (41.5%) and recovery time of up to 30 days (36.6%). Loss of joint mobility, strength and/or muscle mass and increased fatigue were the most described physical consequences (29.0%, 20.3% and 20.3%, respectively) and among the psychological ones, the majority reported fear of suffering the injury again (52.1%). No significant difference was observed between the dimensions of quality of life and subjective perception of pain between practitioners with and without injuries. However, the sampled individuals who reported having suffered an injury while practicing the sport presented a significantly higher index on the Global Sleep Scale [7 (2-14)] than those without injuries [5.5 (1-9)] (p value = 0.022). Conclusion: There was no association between injuries and lower quality of life and greater subjective perception of pain or functional disability, however, the sleep quality index, in the Global dimension, is associated with the presence of injuries.